ANALISIS PROGRAM COMMUNITY TB CARE ‘AISYIYAH DALAM PERSPEKTIF PENGEMBANGAN MASYARAKAT (Politeknik Kesehatan Kemenkes Bandung, 2022)
Through the TB Care Community program, Aisyiyah seeks to participate in health development in Indonesia and the achievement of the Millennium Development Goals (MDGs) no. 6 target, namely reducing the spread of infectious diseases through community participation in counseling, finding suspects and assisting the treatment of TB patients with the DOTS strategy. The research method used is through a qualitativedescriptive approach, data collection is carried out through in-depth interview techniques with one of the regional leaders of 'Aisyiyah West Java and coupled with secondary data deepening in the form of reports on activities from the TB Care community program 'Aisyiyah. The implementation of the Community TB Care ‘Aisyiyah program has fulfilled the implementation of community development dimensions and principles. The dimensions and principles of community development include the dimensions of Ecology, Social Justice, Local Values, Relationship Processes and Global Local